State capitalism, institutional adaptation, and the Chinese miracle - Naughton, Barry; Tsai, Kellee S. (Cambridge University Press, 2015)
China's stunning growth rates have corresponded with the rise of "state capitalism." Since the mid-2000s, China's political economy has stabilized around a model where most sectors are marketized and increasingly integrated with the global economy; yet strategic industries remain firmly in the grasp of an elite empire of state-owned enterprises. What are the implications of state capitalism for industrial competitiveness, corporate governance, government-business relations, and domestic welfare? How does China's model of state capitalism compare with other examples of state-directed development in late industrializing countries? As China enters a phase of more modest growth, it is especially timely to understand how its institutions have adapted to new challenges and party-state priorities. In this volume, leading scholars of China's economy, politics, history, and society explore these compelling issues.-- Provided by publisher
Keywords: Capitalism -- China.; China -- Economic policy -- 2000-; China -- Economic conditions -- 2000-; Chine -- Politique économique -- 2000-; Chine -- Conditions économiques -- 2000-; BUSINESS & ECONOMICS -- Economics -- General.; BUSINESS & ECONOMICS -- Reference.; Capitalism; Economic history; Economic policy; China; Politics and Government.; Since 2000; Electronic books.